2009
DOI: 10.1111/j.1445-6664.2008.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed morphological traits and genotypic diversity of weedy rice (Oryza sativa f. spontanea) populations found in the Thai Hom Mali rice fields of north‐eastern Thailand

Abstract: Weedy rice (Oryza sativa f. spontanea) is a problematic weed in the Thai Hom Mali rice production areas of Thung Kula Ronghai in north-eastern Thailand.There is a great need to initiate studies of weedy rice populations in order to perform basic studies to learn about the seed morphology and genetic diversity. The aims of this study were to determine the seed morphological traits and amylose content and to evaluate the genetic variation, based on the polymorphisms of nuclear and chloroplast DNA, of weedy rice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Phylogenetic and demographic analysis based on whole-genome sequencing revealed that Chinese weedy rice was de-domesticated independently from the cultivated rice, standing variations and new mutations contributed differently to the rapid adaptation of japonica and indica type of weedy rice from four representative regions of China (Qiu et al 2017). Similar results were found for the origins of weedy rice in Thailand and Bhutan (Prathepha 2009;Ishikawa et al 2005). Notably, crossing experiments involving intersub-specific and inter-varietal hybridization have generated progenies that exhibit weedy rice traits.…”
Section: Origin and Evolutionsupporting
confidence: 58%
See 2 more Smart Citations
“…Phylogenetic and demographic analysis based on whole-genome sequencing revealed that Chinese weedy rice was de-domesticated independently from the cultivated rice, standing variations and new mutations contributed differently to the rapid adaptation of japonica and indica type of weedy rice from four representative regions of China (Qiu et al 2017). Similar results were found for the origins of weedy rice in Thailand and Bhutan (Prathepha 2009;Ishikawa et al 2005). Notably, crossing experiments involving intersub-specific and inter-varietal hybridization have generated progenies that exhibit weedy rice traits.…”
Section: Origin and Evolutionsupporting
confidence: 58%
“…Environmental and other factors, such as the distance between two populations, temperature, relative humidity, flower morphology, and flowering time, also affect the rate of outcrossing (Chen et al 2004;Shivrain et al 2007Shivrain et al , 2009. Introgression of foreign genes into the gene pool of weedy rice can enhance its genetic diversity and could confer some trait modifications that may or may not be of adaptive significance (Cao et al 2006;Gealy et al 2003;Prathepha 2009;Reagon et al 2011;He et al 2014;Goulart et al 2012). Crop-to-weed gene flow is of special concern when transgenes are involved as it leads to the movement of genetically modified (GM) genes to weeds that might confer survival advantages that enable them to outcompete local strains (Oard et al 2000;Lu and Snow 2005;Cao et al 2006;Zhang et al 2006;Yang et al 2012).…”
Section: Outcrossing and Its Associated Concerns In Weedy Ricementioning
confidence: 99%
See 1 more Smart Citation
“…Some weedy rice accessions are morphologically similar to wild rice (Oryza rufipogon) in characteristics such as black hull, red pericarp, low 1000 seed weight, good phenotypic plasticity, high seed shattering and dormancy, and inconsistent maturation time (Oka, 1988;Suh, 2008;Chung, 2010). These characters facilitate the distribution of weedy rice seriously impairing the yield of rice grain (Gressel and Valverde, 2009;Prathepha, 2009;Shivrain et al, 2009;Chung and Park, 2010). Direct-seeded rice systems contribute to the spread of weedy rice, which poses a threat to the rice growers in Asian countries including China, Malaysia, Thailand, India, Korea, the Philippines, Vietnam, and Sri Lanka (Delouche et al, 2007;Varshney and Tiwari, 2008;Prathepha, 2011;Chauhan, 2012;Mansor et al, 2012;Zhang et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…However, those variations showed no association with agro-ecological conditions. Morphological and topographical characteristics of plant organs such as the shape and size of seeds and the structure of incidental features have been useful weapons in identifying and classifying the plant and weed species (Noda et al, 1985;Prathepha, 2009). …”
Section: Seed Morphological Diversitymentioning
confidence: 99%